Dysregulation of MicroRNAs in Hypertrophy and Ossification of Ligamentum Flavum: New Advances, Challenges, and Potential Directions - Zhang, Baoliang; Chen, Guanghui; Yang, Xiaoxi; Fan, Tianqi; Chen, Xi; Chen, Zhongqiang (Frontiers in Genetics, 2021)
Pathological changes of ligamentum flavum (LF) can be defined as a process of chronic progressive aberrations in the nature and structure of ligamentous tissues characterized by increased thickness, reduced elasticity, local calcification or aggravated ossification, which may cause severe myelopathy, radiculopathy, or both. Hypertrophy of ligamentum flavum (HLF) and ossification of ligamentum flavum (OLF) are clinically common entities. Though accumulated evidence has indicated both genetic and environmental factors could contribute to the initiation and progression of HLF/OLF, the definite pathogenesis remains fully unclear. MicroRNAs (miRNAs), one of important epigenetic modifications, are short single-stranded RNA molecules that regulate protein-coding gene expression at post-transcriptional level, which can disclose the mechanism underlying diseases, identify valuable biomarkers and explore potential therapeutic targets. Due to the central role of miRNAs in the regulation of gene expression, we summarized current studies from the point of view of miRNA-related molecular regulation networks in HLF/OLF. Exploratory studies revealed a variety of miRNA expression profiles and identified a battery of up-regulated and down-regulated miRNAs in OLF/HLF patients through microarray datasets or transcriptome sequencing. Experimental studies validated the roles of specific miRNAs (eg. miR-132-3p, miR-199b-5p in OLF, miR-155, miR-21 in HLF) in regulating fibrosis or osteogenesis differentiation of LF cells and related target genes or molecular signaling pathways. Finally, we discussed the perspectives and challenges of miRNAs-based molecular mechanism, diagnostic biomarkers and therapeutic targets of HLF/OLF.